Child Guidance Techniques - Oregon State Univ., Corvallis. Cooperative Extension Service; Oregon State Univ., Corvallis. Cooperative Extension Service; Washington State Univ., Pullman. Cooperative Extension Service; Idaho Univ., Moscow. Cooperative Extension Service ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This booklet discusses the role that parents can play in helping their children mature, make decisions, and adjust to the challenges of the world around them. It suggests that parents and others who take care of children keep in mind the following ideas when interacting with children: (1) focus on "do's" instead of "don'ts"; (2) build feelings of confidence; (3) try to change behavior by changing surroundings or situations; (4) provide choices for children; (5) work with children, not against them; (6) set limits for children; (7) listen to yourself and your child; (8) set a good example; and (9) show love to your children. A parent self-test is provided to review the material covered in the booklet. (MDM)
ERIC Note: A Pacific Northwest Extension publication.
Parents.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Child Rearing; Discipline; Early Childhood Education; Guidance; Parent Child Relationship; Parent Education; Parent Materials; Parent Role; Parenting Skills; Parents as Teachers; Role Models; Self Esteem; Guides, Non-Classroom.